2001
DOI: 10.1103/physreve.64.052202
|View full text |Cite
|
Sign up to set email alerts
|

Experimental estimate of energy accommodation coefficient at high temperatures

Abstract: The energy accommodation coefficient (EAC), which is used to characterize gas-surface interactions, was experimentally estimated at high temperatures. A method utilizing laser irradiation to heat up nanoparticles that are generated in a flame was proposed. From the obtained dependence of particle temperature upon laser power, the EAC was derived to be approximately equal to 0.005, which agrees nicely with our recent rigorous theoretical result. It indicates that the efficiency of heat transfer between gas and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The authors were able to solve this puzzle using the small energy accommodation coefficient (EAC) in their heat balance model. Note that this small EAC was theoretically predicted and experimentally demonstrated in previous work [5,6], and it was successfully utilized for the modeling of the nanoparticle growth in different systems [7,8,9].…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…The authors were able to solve this puzzle using the small energy accommodation coefficient (EAC) in their heat balance model. Note that this small EAC was theoretically predicted and experimentally demonstrated in previous work [5,6], and it was successfully utilized for the modeling of the nanoparticle growth in different systems [7,8,9].…”
Section: Introductionmentioning
confidence: 59%
“…The asymptotically vanishing value of EAC at high temperatures was derived from the rigorous quantum mechanics model [5] describing energy transfer to the phonon system which distribution does define the temperature of not only solids, but that of liquids as well [16]. The small EAC value (<0.005) was demonstrated in the experiment [6]. At the same time, there is a belief that the EAC of the order of 0.1–1 claimed to be measured by the laser-induced incandescence (LII) technique [17,18] should be used instead.…”
Section: Remarks On Eacmentioning
confidence: 99%
“…where E is the total energy transferred to the wall and ∆h f the dissociation energy of the recombined molecule. Models of the accommodation coefficient can be found in literature [23][24][25]. On the other hand, the roughness of the surface increases the wet area on which the atomic species can collide and recombine.…”
Section: The Macroscopic Descriptionmentioning
confidence: 99%
“…To the best of our knowledge, there are no studies available in the literature on thermal accommodation of oxygen and nitrogen on metal oxide surfaces at elevated temperatures. Probably, the only exception is the work of Altman et al 47 who studied the silica nanoparticles at conditions close to those existing in combustion (temperatures around 2000 K) and found that the accommodation coefficient does not exceed the value of 0.005.…”
Section: -9mentioning
confidence: 99%